NIMG-25. TRANSFERRIN RECEPTOR 1 TARGETED PET/CT AND NIFR PROBES FOR IMAGING GLIOBLASTOMA MOUSE MODELS. (9th November 2020) - Ni, Xiang-Rong; Zhao, Yi-Ying; Cai, Hai-Ping; Yu, Zhi-Hui; Wang, Jing; Chen, Fu-Rong; Yu, Yan-Jiao; Feng, Guo-Kai; chen, Zhong-ping
Abstract: OBJECTIVE: A new imaging technology that indiscriminately detects intracranial glioblastoma (GBM) can help neurosurgeons remove tumor mass completely. Transferrin receptors (TfR 1) have been widely investigated as a diagnostic and therapeutic target in GBM. A TfR 1-targeted peptide, CRTIGPSVC (CRT) can accumulate at high levels in GBM tissues. In our study, taking the advantage of CRT, we synthesized two molecular imaging probes for imaging GBM precisely. One is a PET/CT probe 18 F-NOTA-CRT, and the other is a near-infrared fluorescent (NIFR) probe Cy5-CRT. METHODS: We initially confirmed the overexpression of TfR 1 in most of GBM and the tumor-specific homing ability of 18 F-NOTA-CRT and Cy5-CRT in orthotopic U87 GBM (TfR 1 overexpression) mouse models. We then examined the feasibility of Cy5-CRT for specially identifying the GBM tissue margin in the intracranial U87 xenografts in vivo and ex vivo. Next, we compared Cy5-CRT with the clinically used fluorescein sodium in identifying tumor margins. Finally, we used Cy5-CRT to carry out a fluorescence-guided operation on a orthotopic U87 mouse model. RESULTS: Both 18 F-NOTA-CRT and Cy5-CRT probes specifically accumulated in U87 GBM xenografts with TfR 1 overexpression, but not in U373 GBM xenografts with very low TfR 1 expression. Cy5-CRT detected the intracranial tumor burden with exceptional contrast, enabling fluorescence-guided GBM resection under NIFR live imaging conditions. Importantly, Cy5-CRT recognized the GBM tissue margin more clearly than fluorescein sodium. CONCLUSIONS: Our probes were capable of thoroughly detecting GBM tissue in vivo imaging. For translational applications, we may screen patients before surgery by PET/CT imaging with 18 F-NOTA-CRT to identify gliomas with TfR 1 overexpression. As for fluorescence-guided surgery, the TfR 1-targeted optical probe Cy5-CRT specifically differentiates tumor tissues from normal brain with high sensitivity, indicating its potential application for the precise surgical removal of GBM. Keywords: Transferrin receptor 1; PET/CT; near-infrared fluorescence imaging; glioblastoma, fluorescence-guided surgery